Analyzing Digital Twin Adoption in Aluminum Plants Using Technology Readiness Index 2.0 - Yusuf Nugroho Doyo Yekti; Wiyono Sutari; Nur Ichsan Utama; Murman Dwi Prasetio (International Journal of Innovation in Enterprise System, 2024)
In the era of industrial digitalization, Digital Twin technology offers a potential solution to enhanceefficiency and innovation. This study investigates the readiness of workers in an Indonesian aluminumcasting plant to embrace new technology, considering their perceptions of optimism, innovation,discomfort, and insecurity. A semi-quantitative approach was employed, utilizing the TechnologyReadiness Index (TRI) 2.0. The research involved four representatives selected by the industry'sleadership. Questions were specifically designed to assess the readiness for Digital Twin technologyin the aluminum casting plant. The data were analyzed using content analysis to determine the overallreadiness for new technology and the characteristics of key personnel for Digital Twin technology.The overall Technology Readiness Index (TRI) 2.0 score indicated a grand mean of 3.75 (SD: 0.74),suggesting that the employees generally tend to be skeptical but slightly inclined towards a positiveattitude in accepting Digital Twin technology for implementation in the aluminum casting plant.